2018
DOI: 10.3390/nu10091300
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Vitamin E Status and Associated Pregnancy Outcomes in Maternal–Infant Dyads between a Nigerian and a United States Population

Abstract: Oxidative stress is associated with adverse pregnancy outcomes, and vitamin E has powerful anti-oxidant properties with the potential to impact health outcomes. Tocopherol isomers of vitamin E differ in their ability to modulate inflammation and vary in concentration in diets containing high proportions of processed versus unprocessed foods. The purpose of this study was to compare vitamin E status and associated pregnancy outcomes (mode of delivery, chorioamnionitis, APGARs (measure of appearance, pulse, grim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 33 publications
0
20
1
Order By: Relevance
“…γ-Tocopherol also decreases lipid peroxidation (weaker than α-tocopherol) and neutrophilic inflammation (stronger than α-tocopherol), but it can promote type 2 inflammation (18,19) . The latest early life study in both Nigerian and American maternal-neonatal dyads reported the association between decreased circulating α-:γ-tocopherol and negative birth outcomes such as Caesarian sections (20) . The ratios of α-:γ-tocopherol could contribute to a more comprehensive understanding of the infant's vitamin E requirements than α-tocopherol alone, but the ratios in human milk still lack investigation.…”
mentioning
confidence: 99%
“…γ-Tocopherol also decreases lipid peroxidation (weaker than α-tocopherol) and neutrophilic inflammation (stronger than α-tocopherol), but it can promote type 2 inflammation (18,19) . The latest early life study in both Nigerian and American maternal-neonatal dyads reported the association between decreased circulating α-:γ-tocopherol and negative birth outcomes such as Caesarian sections (20) . The ratios of α-:γ-tocopherol could contribute to a more comprehensive understanding of the infant's vitamin E requirements than α-tocopherol alone, but the ratios in human milk still lack investigation.…”
mentioning
confidence: 99%
“…α-Tocopherol, a major composition moiety of vitamin E, is an important compound in the maintenance of reproduction activity and reputed for its antioxidative activity ( Rimbach et al, 2010 ). It could influence the whole process of reproduction, including the health condition of pregnant women, pregnancy outcome, embryotic development, neonatal development, and so on ( Cave et al, 2018 ). However, in the present study, only a modest increase was observed in alpha-tocopherol succinate.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this vitamin is capable to reduce and counteract oxidative stress during pregnancy, lowering the risk of preeclampsia and preterm birth [180]. Vitamin E levels in maternal blood are also correlated with improved fetal growth [181]. However, high doses of vitamin E (≥400 IU/day) are associated with an apparent decrease in birth weight, and its administration is suggested during the first trimester of pregnancy [182].…”
Section: Zinc (Zn)mentioning
confidence: 99%